Efektivitas Pengawasan Balai Besar Pengawas Obat Dan Makanan (Bbpom) Dalam Peredaran Kosmetik Berbahaya Di Kota Makassar - Febriani, Eka; Razak, Andi Rosdianti; Malik, Ihyani (Universitas Muhammadiyah Makassar, 2022)
This study discussed the Effectiveness of Supervision of the Center for Drug and Food Control in the Distribution of Dangerous Cosmetics in Makassar City. The purpose of this study was to find out how effective the Makassar POM Center Supervision was in the distribution of dangerous cosmetics. This study used descriptive qualitative method. Data collection techniques used observation and interview techniques. The technique of validating data was triangulation based on the theory of Steers (1985) with indicators of Goal Achievement, Integration and Adaptation. The results showed that the supervision carried out by BPOM in the distribution of dangerous cosmetics in Makassar City was quite effective. This seen from the indicators used, namely: 1) Achieving goals, BPOM had been effective in the process of achieving goals because the planned targets run well according to plan, 2) Integration, BPOM was able to provide socialization and training in the distribution of dangerous cosmetics, 3) Adaptation , it was effective because it could adapt to the time. Keywords: Effectiveness, Supervision, Circulation, Cosmetics